Effect of Omega-3 Enriched Layer Rations on Egg Quality - Dunn-Horrocks, S.; Pichardo-Fuchs, M.; Lee, J.; Ruiz-Feria, C.; Creger, C.; Hyatt, D.; Stringfellow, K.; Sanchez, M.; Farnell, M. (International Journal of Poultry Science, 2010)
Human consumption of omega-3 Polyunsaturated Fatty Acids (n-3 PUFA) has increased due to reported health benefits. Despite the benefits of n-3 PUFA eggs, the addition of omega-3 enriched feedstuffs like flaxseed and fish oil may reduce egg quality. A standard n-PUFA diet containing flaxseed and fish oil (Diet A), a standard n-PUFA diet supplemented with vitamin B6 (Diet B), a standard n-PUFA diet without fish oil (Diet C) and a conventional milo ration (Diet D) were fed to four separate groups of laying hens to evaluate the effect of these diets on egg quality. Three individual shipments of eggs collected from hens fed these diets were received from a commercial layer operation, where these hens were reared. The eggs were stored for three weeks in a refrigerator to simulate consumer storage conditions. The eggs were evaluated for quality by determining whole egg weight, yolk weight, albumen thickness and Vitelline Membrane Strength (VMS). Significant increases in egg weights were observed in Diet B samples in the first egg shipment and Diets B, C and D in the third egg shipment. Yolk weights were significantly increased with Diet B samples from the third collection. No differences were observed in albumen thickness in any of the three shipments of eggs. Numerical increases in VMS were observed in Diets B, C and D in each of the three shipments, but only the third shipment had significant differences with these treatments. These data suggests that the addition of flaxseed and fish oil may negatively affect egg quality. The addition of vitamin B6 or the removal of fish oil to a standard n-PUFA diet may be comparable to a conventional layer ration’s effect on egg quality.